ChemInform Abstract: Duality of Donor—Acceptor Cyclopropane Reactivity as a Three‐Carbon Component in Five‐Membered Ring Construction: [3 + 2] Annulation versus [3 + 2] Cycloaddition. Issue 41 (19th September 2013) - Volkova, Yulia A.; Budynina, Ekaterina M.; Kaplun, Alexey E.; Ivanova, Olga A.; Chagarovskiy, Alexey O.; Skvortsov, Dmitriy A.; Rybakov, Victor B.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract A new simple approach to the synthesis of cyclopentannulated (hetero)arenes is developed.